Desempenho agronômico de genótipos de soja e identificação de locais para a condução de ensaios multi-ambiente na região sul do Brasil - Dalló, Samuel Cristian (2018)
Productivity increases in soybean crop over the years are the result of the constant efforts of breeding programs to provide more productive and adapted cultivars to producers. Each year hundreds of strains are evaluated in multi-environment trials by breeding programs to identify the genotypes best suited to each region of interest. In this sense, knowing the adaptability and stability of the genotypes in each target region, as well as, the best test sites, are fundamental for the increments of crop productivity. Thus, the objective of this work was to identify the best test sites for conducting multi-environment trials for soybean in southern Brazil, as well as to identify the best soybean genotypes for each region and edaphoclimatic cultivation. Data from cultivation and use value (VCU) trials conducted between the 2012-13 and 2016-17 harvests were used. All assays were conducted in a randomized complete block design with three replicates. The statistical analyzes were performed with the GGEBiplot software. The best venues for conducting VCU trials are: Macroregion 01, REC 101: Cachoeira do Sul; REC 102: Ronda Alta, Passo Fundo, Santa Bárbara do Sul and Ciríaco; and REC 103: Castro. Macroregion 02, REC 201: Rolândia, Marechal Cândino Rondon, Campo Mourão, Santa Terezinha de Itaipu, Palotina, Floresta and Londrina; REC 202: Navirai; and REC 204: Ponta Porã and Maracajú. The genotypes closest to the ideal were: Macroregion 01, REC 102: genotype 68I70RSF IPRO; REC 103: 54I52RSF IPRO and NS 5959 IPRO genotypes. Macroregion 02, REC 201: Genotype 63I64RSF IPRO, REC 204: genotypes 7166RSF IPRO, 63I64RSF IPRO and M6210IPRO. The 68I70RSF IPRO genotype presented the highest RG in the Santa Bárbara do Sul and Passo Fundo sites in REC 102. In REC 103 the 54I52RSF IPRO genotype was the best in Castro and the NS 5959 IPRO genotype the best in Castro and Vacaria. In REC 201, genotype 63I64RSF IPRO showed the highest RG in the Mamborê, Marechal Cândido Rondon and Londrina sites in 2013, 2014 and 2015, respectively, and at REC 204 in Dourados, genotypes 7166RSF IPRO, 63I64RSF IPRO and M6210IPRO had the highest RG in 2013, 2014 and 2015, respectively.